2014
DOI: 10.5539/ijbm.v10n1p80
|View full text |Cite
|
Sign up to set email alerts
|

Creating Brand Equity by Leveraging Value Creation and Consumer Commitment in Online Brand Communities: A Conceptual Framework

Abstract: Advancement in information technologies has created change in our economics as well as in our societies because companies strive to adapt the conditions that prevail in marketplace. In this scenario, marketing professionals are exploring advanced and effective ways to build a strong brand. The research objectives explore the impact of online brand communities on brand equity dimensions through which consumer could achieve commitment and value-creation. While, marketing managers could explore attributes regardi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 57 publications
1
12
0
Order By: Relevance
“…Extensive research has identified the critical roles of VCC in facilitating brand equity. For instance, Zhang et al (2015) find that leveraging VCC patterns strategically is a useful and advanced way to improve brand perception, brand loyalty and relationship satisfaction. García Haro et al (2014) have debated the internal and external effects of VCCs on companies, ranging from improved product quality, increased productivity, reduced costs and popularized product acceptance to the company's public reputation.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…Extensive research has identified the critical roles of VCC in facilitating brand equity. For instance, Zhang et al (2015) find that leveraging VCC patterns strategically is a useful and advanced way to improve brand perception, brand loyalty and relationship satisfaction. García Haro et al (2014) have debated the internal and external effects of VCCs on companies, ranging from improved product quality, increased productivity, reduced costs and popularized product acceptance to the company's public reputation.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…As for the relationship between IMC and brand loyalty, Keller (2009) argued that maintaining consistent brand messages and image has a strong effect on improving brand loyalty, while Šerić et al (2014) claimed that an optimal combination of effective communication disciplines can help keep existing customers while reinforcing their loyalty. Zhang, Shabbir, Pitsaphol, and Hassan (2015) provided empirical evidence that IMC positively affects customer loyalty. Likewise, Šerić et al (2020) recently demonstrated that communication consistency has a strong direct impact on brand loyalty with fast-food brands.…”
Section: Imc and Brand Loyaltymentioning
confidence: 99%
“…Thus, the utilization of consumer-brand and consumer-consumer relationships has become CE's major innovative role to strategically establish sustainable advantage for SBE building (Chan, Boksem & Smidts, 2018). The optimization of CE interactivities is to create high BA in familiarization criteria (Zhang, Shabbir, Pitsaphol & Hassan, 2015;Islam & Rahman, 2016). On the contrary, brand associations develop positive attitudes towards a product and non-product dimensions in functional, performance-related, and imagery-related retrieved in the image perceived (Keller, 1993(Keller, , 2001).…”
Section: Brand Loyalty As a Mediator In The Causal Relationshipsmentioning
confidence: 99%